Pengujian Kadar Pengawet Asam Benzoat dan Asam Sorbat Pada Permen Keras Menggunakan Kromatografi Cair Kinerja Tinggi: Determination of Benzoic Acid And Sorbic Acid Preservative Levels In Hard Candies Using High-Performance Liquid Chromatography - Samara, Reizza Muhammad Giyats Al Hisyam Dwi; Yuningsih, Nuning; Putri, Nezly Nurlia (Universitas Bumigora, 2023)
Hard candy is a solid snack made from sugar or other sweeteners, sometimes with added food ingredients and food additives (BTP). According to BPOM Regulation No. 11 of 2019, the maximum allowable levels of benzoic acid and sorbic acid in hard candy are 500 mg/kg and 1000 mg/kg body weight. Excessive consumption of these acids can pose health risks. Food quality control of the use of BTP can be done by routine testing in the laboratory. One of the instruments that can detect BTP is High-Performance Liquid Chromatography (HPLC). This study aims to analyze the levels of benzoic acid and sorbic acid in hard candy samples using an HPLC. The results showed that neither benzoic acid nor sorbic acid was detected in the samples. The LOD value of benzoic acid obtained on the HPLC instrument was 4.92 mg/kg, and the LOD of sorbic acid was 3.70 mg/kg) which limits its use to meet BPOM regulation No. 11 of 2019. The testing process for benzoic acid and sorbic acid in hard candy samples is also correct and by the procedure, where the recovery value is in the range of 90-107%, the RPD value is smaller than the 2/3 CV Horwitz value (In benzoic acid, the RPD value is 1.02% and the CV Horwitz value is 6.42 while in sorbic acid the RPD value is 0.75% and the CV Horwitz value is 4.15) with a correlation coefficient that meets the linearity (r) requirement of 0.9999.